Intra-individual variability in the sleep of senior and junior rugby league athletes during the competitive season - Caia, J.; Halson, S. L.; Scott, T. J.; Kelly, V. G. (Chronobiology International, 2017)
This study examined the sleep intra-individual variability (IIV) of rugby league athletes across senior and junior levels during one week of the competitive season. Forty-five rugby league athletes across elite senior, sub-elite senior and elite junior levels each wore actigraphy monitors for seven days during the competitive season, and completed a subjective sleep diary each morning upon waking. Linear mixed models were used to assess differences in sleep measures between playing levels. Intra-individual standard deviations for each sleep measure were calculated for each athlete to determine their respective IIV, allowing differences in IIV between groups to be assessed. Elite junior athletes went to bed later (ES = 0.94 ± 0.50, p < 0.05) and woke later than elite senior athletes (ES = 0.94 ± 0.40, p < 0.05), while also displaying greater IIV when considering time in bed (ES = 1.14 ± 0.60, p < 0.05) and sleep duration (ES = 1.53 ± 0.64, p < 0.05) compared with elite senior athletes. Similarly, IIV was more pronounced in elite junior players for time in bed (ES = 0.88 ± 0.60, p < 0.05) and sleep duration (ES = 1.03 ± 0.64, p < 0.05) compared with sub-elite senior athletes. Despite this, elite junior athletes still obtained sufficient sleep duration, efficiency and quality. The outcomes of this investigation show a distinct difference in the habitual sleep-wake patterns of senior and junior rugby league athletes, and show how sleep IIV differs between playing levels in rugby league.